2019
DOI: 10.1177/0960327119842241
|View full text |Cite
|
Sign up to set email alerts
|

Effect of EH domain containing protein 2 on the biological behavior of clear cell renal cell carcinoma

Abstract: To investigate the effects of EH domain containing protein 2 (EHD2) on clear cell renal cell carcinoma (ccRCC) and provide new insights for the clinical treatment of rental cancer. Forty patients (26 males and 14 females, 62.4 ± 5.7 years old) with ccRCC were selected from January 2015 to December 2016 to serve as research subjects in this study. The EHD2 protein expression in the tumor tissues and adjacent healthy tissues of ccRCC patients were detected by Western Blot assay. The cells of ccRCC cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…It was confirmed that circEHD2 knock-down reduced SU-resistant cancer cells’ progression. Our study is in agreement with a previous investigation which confirmed that EHD2 elevation enhances RCC proliferation, migration and invasion [ 26 ]. Several studies have confirmed that circRNA has multiple sites to bind and control miRNA activity and modulate downstream target genes.…”
Section: Discussionsupporting
confidence: 94%
“…It was confirmed that circEHD2 knock-down reduced SU-resistant cancer cells’ progression. Our study is in agreement with a previous investigation which confirmed that EHD2 elevation enhances RCC proliferation, migration and invasion [ 26 ]. Several studies have confirmed that circRNA has multiple sites to bind and control miRNA activity and modulate downstream target genes.…”
Section: Discussionsupporting
confidence: 94%
“…EHD2 knockdown promotes cell migration in oesophageal squamous cell carcinoma ( 48 ). Extensive studies have shown that lncRNAs containing miRNA binding sites can function as ceRNAs to regulate mRNAs in cancers, including OS ( 49 - 51 ). The ceRNA pattern mediated by TUSC8 also functions in other types of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, Liu et al demonstrated that EHD2 overexpression enhanced the proliferation, invasion, and migration but inhibited the apoptosis of clear cell renal cell carcinoma (ccRCC) cells, while EHD2 interference showed opposite functions. Interference of EHD2 can inhibit the development of ccRCC by inhibiting the cellular proliferation, invasion, and migration ( 26 ). In addition, EHD2 overexpression inhibits colon cancer cell proliferation, but enhances cell apoptosis and cell cycle arrest ( 15 ).…”
Section: Discussionmentioning
confidence: 99%